Perioperative Considerations for a Patient with a Left Ventricular Assist Device Undergoing Thyroidectomy - Sharma, Avijit (Cureus, 2020)
As the population ages, ventricular assist devices (VADs) are becoming more prevalent, even in the outpatient perioperative setting. Patients with VADs present unique challenges for the anesthesiologist, who needs to have a thorough understanding of device physiology and design an appropriate anesthetic plan. This case report demonstrates an alternative monitored anesthesia care (MAC) anesthetic technique for a patient with a left VAD undergoing total thyroidectomy. This alternative provided a safe comfortable anesthetic and can be used successfully in patients with circulatory support devices.